2018
DOI: 10.1159/000493807
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Characteristics of de novo Renal Cryoglobulinemia After Direct-Acting Antivirals Treatment in an Egyptian Hepatitis C Cohort

Abstract: Introduction: The side effects profile of the new direct-­acting antivirals for the treatment of hepatitis C virus (HCV) is not fully elucidated. Objective: In this cross-sectional study, we aim to describe the incidence and characteristics of a novel observation of de novo renal cryoglobulinemic glomerulonephritis after successful treatment with DAA. Methodology: A total of 12,985 Hepatitis C Patients (genotype IV) received the new DAA. After successful treatment, patients with deranged renal functions or pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Two thousand articles were initially identified through database-searching on PubMed, Embase, Cochrane, Web of Science, and clinicaltrials.gov. Ultimately, 19 studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] meeting the prespecified inclusion criteria were selected (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two thousand articles were initially identified through database-searching on PubMed, Embase, Cochrane, Web of Science, and clinicaltrials.gov. Ultimately, 19 studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] meeting the prespecified inclusion criteria were selected (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Clinical relapse was reported when there was a recurrence of purpura, arthralgia/arthritis, neuropathy, or nephropathy after CR or PR. Serological relapses were defined by cryoglobulins >1.5%, elevated rheumatoid factor (RF), or detectable complement 4 (C4) after the in- Out of the 19 included studies, the CryoVas response and relapse rates were provided in 14 studies and are summarized in Table 1 [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. It includes data from 11 prospective cohort studies, 2 retrospective cohort studies, and 1 cross-sectional study.…”
Section: Hcv-related Cryovas Response With Daamentioning
confidence: 99%
See 1 more Smart Citation
“…However, given that multiple studies have shown the DAAs are efficacious in patients with CGN (29,30), it is now recommended per KDIGO guidelines that DAAs be used as first line treatment for cryoglobulinemic glomerulonephritis and that immunosuppression with rituximab-based therapy be reserved for patients with severe manifestations of vasculitis (rapidly-progressive glomerulonephritis, pulmonary hemorrhage) or those with persistent glomerulonephritis after completing DAAs (31). It is important to note that de novo cryoglobulinemic glomerulonephritis can occur after cure of HCV with DAAs, though the incidence is rare (32). In this instance, rituximab-based immunosuppression treatment should be used.…”
Section: Hcv and Chronic Kidney Diseasementioning
confidence: 99%
“…A summary of "real-world" use of DAAs in kidney transplant recipient confirmed high cure rates (97%) and low acute rejection rates (3%) (50). HCV-related post-transplant glomerulonephritis is likely to be less common in transplant recipients who have received DAAs, however it is important to note that de novo cryoglobulinemic glomerulonephritis has been described in HCV-infected patients who have been cured of HCV (32).…”
Section: Hcv In Kidney Transplant Recipientsmentioning
confidence: 99%